Cardiotoxicity in Biological Agent-Targeted Therapy for Rheumatoid Arthritis: ADR Signal Mining and Analysis of Food and Drug Administration Adverse Event Reporting System Database - Tang, Xiaoyan; Xu, Xiaolin; Li, Ji; Zhao, Bin (Frontiers in Pediatrics, 2021)
Purpose: Biologic agents-induced cardiotoxicity is concerning. Biologic agents are known to have potential for cardiotoxicity for rheumatoid arthritis (RA), but existing trial evidence is inadequate to understand real-world patterns of cardiotoxicity. To quantify the risk of cardiotoxicity in patients with rheumatoid arthritis treated with biologic agents. Methods: The cardiotoxicity reports induced by 4 kinds of biologic agents as “abatacept” ， “adalimumab” ，“tocilizumab and “etanercept” were used as the first suspected dugs to collected from FDA adverse event reporting system(FAERS) database during Jan. 1st，2004-Sep 30st，2020. Reports of cardiotoxicity events were analyzed with the reporting odds ratio (ROR) algorithm, the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN), the multi-item gamma Poisson shrinker (MGPS) and logistic regression methods. The Medical Dictionary for Regulatory Activities Preferred Terms was used to identify such events. Results: A total of 3969 reports of cardiotoxicity events were identified with biologic agents for RA as the suspect drug in this study, involving 317 reports of abatacept，2137 reports of adalimumab，273 reports of tocilizumab， and 1242 reports of etanercept. Adalimumab had the highest number of reports followed by etanercept. Proportions of reports of death and disability outcomes for each targeted therapy were approximately 20–25% of the total reports of serious events. Relatively low cardiotoxicity reporting rates were found with abatacept. Conclusions: Analysis of FAERS data provides more precise profile on the occurrences and characteristics of cardiotoxicity events. The findings remind clinical doctors pay more attention on surveillance, and comparative studies are needed in the future to explain the mechanisms that cause these phenomena.